Determinants of Audit Report Lag with Auditor Reputation as a Moderating Variable (E-Jurnal Akuntansi, 2026)
This study examines the effects of financial distress, institutional ownership, tax avoidance, and audit tenure on audit report lag, with auditor reputation as a moderating variable, in consumer cyclicals sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The research sample was obtained through purposive sampling and yielded 132 units of analysis. The research method used Moderated Regression Analysis (MRA). The results show that financial distress has a positive effect on audit report lag, while institutional ownership, tax avoidance, and audit tenure have no effect on audit report lag. Auditor reputation mitigates the effects of tax avoidance and institutional ownership on audit report lag but does not moderate the effects of financial distress and audit tenure on audit report lag. Additionally, leverage, as a control variable, has a negative effect on audit report lag. These findings indicate that a company’s financial condition and auditor quality are critical factors in determining the timeliness of audit completion.
Keywords: Audit Report Lag; Financial Distress; Institutional Ownership; Tax Avoidance; Audit Tenure